2011
DOI: 10.1111/j.1863-2378.2009.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Sushi in Pregnancy, Parasitic Diseases – Obstetrician Survey

Abstract: Parasites from raw fish can lead to a wide range of clinical manifestations and can be challenging to treat in pregnancy as result of medication exposure of the foetus. We surveyed obstetrician-gynecologists (ob-gyns) in the U.S. to determine their knowledge about the consumption of raw fish during pregnancy. In March 2007, a questionnaire was mailed to members of the American College of Obstetricians and Gynecologists (ACOG) randomly selected to represent all members. Non-responding physicians were sent two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…26 They are also advised to avoid raw fish (such as sushi or sashimi) because it is more likely to contain parasites or bacteria than cooked fish. 27 Some worry about ecological harms from overfishing or pollution from poorly managed farmed fisheries. 28 In a review of the issues surrounding fish consumption, Oken et al 28 found that there were 21 unique major seafood consumption guidelines or advisories from governments (state and national), nonprofit, and other nongovernmental organizations that targeted various North American populations.…”
Section: Background/introductionmentioning
confidence: 99%
“…26 They are also advised to avoid raw fish (such as sushi or sashimi) because it is more likely to contain parasites or bacteria than cooked fish. 27 Some worry about ecological harms from overfishing or pollution from poorly managed farmed fisheries. 28 In a review of the issues surrounding fish consumption, Oken et al 28 found that there were 21 unique major seafood consumption guidelines or advisories from governments (state and national), nonprofit, and other nongovernmental organizations that targeted various North American populations.…”
Section: Background/introductionmentioning
confidence: 99%